Molecular and Phylogenic study of some Gastrointestinal Bacteria and Viruses associated with Cancer in the South area of Iraq - Hamza Abbas, Hawraa; Abdulrazzaq Gati Al nasery, Mohannad; abdulhussein jarullah, Basim (University of Thi-Qar Journal of Science, 2022)
This study investigated the diagnosis the bacteria that associated with GIT cancer and GIT diseases. A total number of 200 blood and biopsy samples were collected during the period from September 2020 to June 2021. Samples included 100 sample for gastrointestinal cancer patients, 50 for healthy people, and 50 for gastrointestinal patients. Gastrointestinal tract diseases patients were diagnosed clinically, and the disease was evaluated by specialist physicians, presented with dyspepsia referred to the Esophago Gastroduodeno Scope Unit for endoscopy at AL-Hussein teaching hospital (Consulting digestive tract). In the current study, three types of bacteria were diagnosed which relate to diseases of the digestive system, including: Streptococcus bovis spp gallolyticus, Fusobacterium nucleatum, Porphyromonas gingivalisbutby by usig PCR technique. It was found that the highest percentage was for patients with cancer. The results revealed, three types of viruses were diagnosed that are related to diseases of the digestive system, with regard to viruses, including: Human papilloma viruses (HPVs), the Epstein-Barr virus (EBV), Polyoma virus (MCPV) and Human herpes virus (HHV) by PCR technique. However the percentage of the existence of these viruses was higher in patients with cancer than in patients with GIT disease. The DNA sequencing analysis showed a clear genetic variation between bacteria associated with GIT cancer based on 16SrRNA gene according to phylogenetic tree analysis that analyzed compared Standard NCBI-BLAST but in viruses associated with GIT cancer based on specific gene according to phylogenetic tree analysis compared Standard NCBI-BLAST.